PENYESUAIAN SOSIAL PENYANDANG DISABILITAS TUBUH DI BALAI BESAR REHABILITASI SOSIAL BINA DAKSA (BBRSBD) PROF. DR. SOEHARSO KOTA SURAKARTA, JAWATENGAH - Utomo, Lukman Prasetyo (KOMUNITAS, 2019)
Final Scientific Writing is based on research about Social Adjustment of Disabled People at Social Rehabilitation House ofBinaDaksa (BBRSBD) of Prof. Dr. Soeharso Surakarta. The objectives of the research are to obtain the description about: the characteristics of respondents and 5 aspects of social adjustment namely: recognition, participation, social approval, altruism, and conformity. The method used in this research was descriptive research method with quantitative approach;it aimed to describe the Social Adjustment of Disabilities People at Social Rehabilitation House of BinaDaksa (BBRSBD) of Prof. Dr. Soeharso Surakarta. Data collection techniques used werequestionnaires, observations, and documentation studies. The research was conducted on 34 respondents determined by census. The results showed that the characteristics of respondents consisted of 10 women and 24 men among the ages of 17-25 years. The result of research also showed that 5 aspects of social adjustment, namely recognition aspect 94,12% are in high category so that it needs to be maintained, participation aspect 52,94% is in medium category so that it needs to be improved, social approval aspect 50.00% is in high category and 50.00% is in the moderate category so it needs to be improved, altruism aspect 73.53% is in high category so it needs to be maintained, conformity aspect 85,30% is in high category so it needs to be maintained. Based on the results of research, the participation and social approval aspects are in the moderate category, so they need to be improved by taking into account the problems faced and the source system that can be utilized, the writer offers problem solving in the form of "Participation Enhancement Program and Social Approval for Disabled People through Self-help Group (selfhelp group) at Social Rehabilitation House of BinaDaksa (BBRSBD) of Prof. Dr. Soeharso Surakarta. ". This program aims to improve the realization of better social adjustment for people with disabilities.